2019
DOI: 10.21273/hortsci13713-18
|View full text |Cite
|
Sign up to set email alerts
|

The Quality Evaluation of Tea (Camellia sinensis) Varieties Based on the Metabolomics

Abstract: The identification and evaluation of tea [Camellia sinensis (L.) O. Kuntze] germplasm resources are of great significance for tea plant breeding. In recent years, various methods, such as morphology, biochemistry, molecular markers, and sensory evaluation, have been used to evaluate the tea germplasm resources. However, the evaluation of tea germplasms based on metabolomics is rarely reported. In this study, we first measured the main agronomic characters and biochemical comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
15
1
1
Order By: Relevance
“…The uniformly sized one-year-old seedlings of C.sinensis (L.) O. Kuntze cv. 'QN3' [50], acquired from Qingdao Agricultural University in Shandong Province of China (36°19′N, 120°23′E), were transplanted into plastic cups filled with sandy loam soil and pH 4.5. The 'QN3' was identified by Prof Zhaotang Ding, Yu wang and etc.…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
“…The uniformly sized one-year-old seedlings of C.sinensis (L.) O. Kuntze cv. 'QN3' [50], acquired from Qingdao Agricultural University in Shandong Province of China (36°19′N, 120°23′E), were transplanted into plastic cups filled with sandy loam soil and pH 4.5. The 'QN3' was identified by Prof Zhaotang Ding, Yu wang and etc.…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
“…Clonal identification is traditionally based on morphological descriptors such as plant shape, stem width, leaf shape, young leaf type, and fruit shape [15,17]. However, as in many out-crossing crops, tea is highly heterozygous with most of its morphological, physiological, and biochemical descriptors showing continuous variation and high plasticity [18,19]. Korir et al reported that morphological traits are associated with drawbacks such as the influences of environment on trait expressions, epistatic interactions, and pleiotropic effects among others despite the value of their advantages [17].…”
Section: Introductionmentioning
confidence: 99%
“…Tea plant cultivar, 'QN3' (Camellia sinensis cv. QN3) is an improved cultivar bred by the Tea Research Institute, Qingdao Agricultural University [43][44][45] . The 2-year-old tea seedling were cultured in growth chamber for 2 weeks with photoperiod (12 h light at 25°C and 12 h dark at 20°C, 75% of humidity) and a light intensity of 18, 000 lx.…”
Section: Methodsmentioning
confidence: 99%